EMPLOYEE ENGAGEMENT AS A CATALYST FOR ORGANIZATIONAL PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Nursyidah Nursyidah (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze employee engagement as a key factor in improving organizational performance through a Systematic Literature Review (SLR) method. A total of 10 national journal articles published between 2019 and 2023 were reviewed using Prisma protocol. The results show that employee engagement positively influences organizational performance through several key variables, including job satisfaction, organizational commitment, motivation, work-life balance, organizational support, and inclusive leadership. Employees who are engaged tend to display extra-role behaviors, such as Organizational Citizenship Behavior (OCB), which strengthen organizational effectiveness. Furthermore, contextual factors such as leadership style and perceived organizational justice also play a significant role in reinforcing engagement. This study highlights the importance of an integrative and sustainable strategy in developing employee engagement as a foundation for achieving superior organizational performance.